Identification of Causes in The Dirty Gas Pipeline in Oil and Gas Delivery Process at Job Pertamina Talisman Jambi Merang - Mahmud Basuki (Industrial Engineering Department, Faculty of Science and Engineering, UIN Sunan Kalijaga Yogyakarta, 2022)
Pigging is a routine maintenance method for cleaning the inner pipe surface. The treatment method uses an object called pig. In the world of piping, there are 4 (four) components that are very important and interrelated in carrying out pigging, namely pig launchers, piping systems, pig receivers, and pigs. Pig Launcher is a tool that is used to fire pigs into piping systems, while pigs are objects that are used according to their functions on surfaces in piping systems. The purpose of this study was to identify the cause of dirty gas pipelines in the oil and gas delivery process at JOB Pertamina Talisman Jambi Merang. From the results of the analysis and discussion, identified causes of dirty gas pipes, namely non-standard work procedures, no commitment to pigging activities from the management, non-standard equipment, use of non-standard and outdated anti-corrosion, lack of training on pigging, and low employee awareness of the importance of pigging.